Rediscovery of Proneura prolongata (Zygoptera: Protoneuridae) and other new Odonata records from Colombian Amazon (2012)
ABSTRACT: As with most taxa present in Colombia, the study of dragonflies is still in its exploratory phase. This paper reports the results of a trip to the Amazon region in order to collect dragonflies. Seven new records for the country were found, including the rediscovery of Proneura prolongata Selys and an undescribed species in the genus Calvertagrion St. Quentin.